Gerakan Literasi Sekolah dalam Meningkatkan Minat Baca - Mirnawati Mirnawati (Program Magister Manajemen Pendidikan Islam Fakultas Ilmu Tarbiyah dan Keguruan Universitas Islam Negeri Raden Fatah Palembang, 2023)
This study aims to explain the literacy movement and its impact on increasing students' interest in reading at MAN I Prabumulih. The School Literacy Movement in increasing students' interest in reading at MAN 1 Prabumulih uses a qualitative research approach and type. That is, research with the aim of describing and analyzing every event, event or phenomenon related to the problem that the researcher discusses. The results of the School Literacy Movement (GLS) research at MAN I Prabumulih in increasing interest in reading include through the habit of reading between before starting lessons (tadarus) for students who are unable to go to the library, muhaarah, memorizing surahs and hadiths, tadarus every Friday at the school mosque. The impact of the School Literacy Movement (GLS) at MAN I Prabumulih is that there are positive things that schools get through this program. In addition to students' interest in reading through active visits to the library, they are also enthusiastic about participating in school madding, placing several collections of books that can be exchanged with other students in the class reading corner, and concrete evidence is the success of students in winning competitions on literacy outside of school. Supporting and Inhibiting Factors for the School Literacy Movement (GLS) in Increasing Students' Interest in Reading at MAN I Prabumulih include reading facilities, funds, student motivation and interest, reading resources, and a variety of reading books.